Faktor-Faktor Pendukung Kompetensi Komunikasi Interpersonal: Studi Kasus pada Mahasiswa Tingkat Pertama di Universitas Paramadina - ., YudhiAlfikalia; Maharani, Anita (Jurnal Ilmu Komunikasi, 2009)
Â Abstract: This research is intended to explore the competence of interpersonal communication as the important factor for the students to express their opinion in the discussion, presentation in class and in oral examination. Based on research, found that the competence of students is relatively low. Also found that there is a different degree of the competence among the students in the different departments. The indicators of interpersonal communication competence are (1) the degree participation in organization, (2) frequency in public speaking, and (3) frequency in class discussion.